2018
DOI: 10.9788/tp2018.1-01
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Stimulus Equivalence on Children’s Food Choice and Preference

Abstract: This study investigated the infl uence of character on food's choices. Eleven preschool children were trained to form two equivalent stimulus classes, each comprising one a cartoon character, a geometric shape, and an abstract symbol. One class had a liked character and the other a disliked character. Three preference tests were conducted where the children had to choose between two identical packages with samples of the same snack, differing only by the label. In Test 1 the labels were symbols of the same cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A further four studies were excluded after full text review using the inclusion and exclusion criteria. The studies that were excluded did not include portion size measurement or estimation aids (McAtamney & Annett, 2009; Santos & Rose, 2018; Smeets & Barnes‐Holmes, 2003; Straatmann et al., 2014). Seven studies published between the years of 2010–2020 were included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further four studies were excluded after full text review using the inclusion and exclusion criteria. The studies that were excluded did not include portion size measurement or estimation aids (McAtamney & Annett, 2009; Santos & Rose, 2018; Smeets & Barnes‐Holmes, 2003; Straatmann et al., 2014). Seven studies published between the years of 2010–2020 were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that EBI has been used to teach a wide variety of academic concepts such as geography (Dixon et al., 2017; LeBlanc et al., 2003), mathematics (Lynch & Cuvo, 1995), geometry (Dixon et al., 2016), reading (Rosales et al., 2014), spelling (De Souza & Rehfeldt, 2013), second language skills (Melvin‐Brown et al., 2022) and numeracy (McLay et al., 2016). In addition, EBI has been used to teach children recycling and waste management skills (Bolanos et al., 2020), identification of emotions of others (Schmick et al., 2018), requesting skills (Still et al., 2015), food choice and preference (Santos & Rose, 2018), and portion size estimation (Arntzen & Eilertsen, 2020; Hausman et al., 2014; Trucil et al., 2015). Furthermore, EBI can be effectively integrated with additional behavior analytic procedures, such as behavioral skills training (BST) and differential reinforcement, as a packaged intervention to strengthen the acquisition of skills (Giannakakos et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A second limitation is that some additional measures are not included. For example, the participants could be asked to taste the water in the water bottles and consecutively rate the pleasantness of the water as in previous studies (Barnes-Holmes et al, 2000;Smeets & Barnes-Holmes, 2003) and more recently with different types of food (dos Santos & de Rose, 2018a). The next step would be to investigate whether the valence can be reversed or changed.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Nesse local é possível promover o aprendizado contínuo para um número elevado de indivíduos, uma vez que ali permanecem grande parte do dia, além de ter a presença dos professores e colegas 28 que podem auxiliar no processo educativo. Algumas abordagens que podem estimular o consumo de frutas e hortaliças na infância são as oficinas de culinária, hortas escolares 29 , exposição repetida 8,29 e personagens animados [30][31] . Destaca-se, em especial, a adição de ingredientes mais saudáveis em produtos alimentícios habitualmente consumidos por crianças, a qual favorece a aceitabilidade sensorial de alimentos com baixa preferência por esse público [21][22] .…”
Section: Introductionunclassified